Growth of Pseudomonas taiwanensis VLB120∆C biofilms in the presence of n‐butanol. Issue 4 (3rd October 2016) - Halan, Babu; Vassilev, Igor; Lang, Karsten; Schmid, Andreas; Buehler, Katja
Summary: Biocatalytic processes often encounter problems due to toxic reactants and products, which reduce biocatalyst viability. Thus, robust organisms capable of tolerating or adapting towards such compounds are of high importance. This study systematically investigated the physiological response of Pseudomonas taiwanensis VLB120∆C biofilms when exposed to n ‐butanol, one of the potential next generation biofuels as well as a toxic substance using microscopic and biochemical methods. Initially P. taiwanensis VLB120∆C biofilms did not show any observable growth in the presence of 3% butanol. Prolonged cultivation of 10 days led to biofilm adaptation, glucose and oxygen uptake doubled and consequently it was possible to quantify biomass. Complementing the medium with yeast extract and presumably reducing the metabolic burden caused by butanol exposure further increased the biomass yield. In course of cultivation cells reduced their size in the presence of n ‐butanol which results in an enlarged surface‐to‐volume ratio and thus increased nutrient uptake. Finally, biofilm enhanced its extracellular polymeric substances (EPS) production when exposed to n ‐butanol. The predominant response of these biofilms under n ‐butanol stress are higher energy demand, increased biomass yield upon medium complements, larger surface‐to‐volume ratio and enhanced EPS production. Although we observed a distinct increase in biomass in the presence of 3% butanol it was not possible to cultivate P. taiwanensis VLB120∆C biofilms at higher n ‐butanol concentrations. Thereby this study shows that biofilms are not per se tolerant against solvents, and need to adapt to toxic n ‐butanol concentrations. Abstract : This study systematically investigated the physiological response of Pseudomonas taiwanensis VLB120∆C biofilms when exposed to n ‐butanol, one of the potential next generation biofuels as well as a toxic substance using microscopic as well as biochemical methods. The predominant response of these biofilms under n ‐butanol stress are higher energy demand, increased biomass yield upon medium complements, larger surface‐to‐volume ratio and enhanced EPS production. Although we observed a distinct increase in biomass in the presence of 3% butanol it was not possible to cultivate P. taiwanensis VLB120∆C biofilms at higher n ‐butanol concentrations. Thereby this study shows that biofilms are not per se tolerant against solvents, and need to adapt to toxic n ‐butanol concentrations.